2022
DOI: 10.3390/ma15207245
|View full text |Cite
|
Sign up to set email alerts
|

Structural Aspects and Intermolecular Energy for Some Short Testosterone Esters

Abstract: Testosterone (17β-hydroxyandrost-4-en-3-one) is the primary naturally occurring anabolic–androgenic steroid. The crystal structures of three short esterified forms of testosterone, including propionate, phenylpropionate, and isocaproate ester, were determined via single-crystal X-ray diffraction. Furthermore, all the samples were investigated using powder X-ray diffraction, and their structural features were described and evaluated in terms of crystal energies and Hirshfeld surfaces. They were also compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…The literature reports the crystal structures of other shorter testosterone esters, along with their corresponding CCDC Refcodes, as follows: propionate (ZZZRCG01) [ 15 ], buciclate (ETEVII) [ 16 ], non-esterified form (TESTON10) [ 17 ], isocaproate, phenylpropionate and one propionate polymorph (with deposition numbers 2192707, 2192708 and 2192706) [ 18 ] and also acetate (TELYEO) [ 19 ]. Apart from testosterone esters, the crystal structures of other testosterone derivatives were also investigated [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature reports the crystal structures of other shorter testosterone esters, along with their corresponding CCDC Refcodes, as follows: propionate (ZZZRCG01) [ 15 ], buciclate (ETEVII) [ 16 ], non-esterified form (TESTON10) [ 17 ], isocaproate, phenylpropionate and one propionate polymorph (with deposition numbers 2192707, 2192708 and 2192706) [ 18 ] and also acetate (TELYEO) [ 19 ]. Apart from testosterone esters, the crystal structures of other testosterone derivatives were also investigated [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Turza et al [ 18 ] showed the structural aspects and intermolecular energy of some short testosterone esters. Testosterone (17β-Hydroxyandrost-4-en-3-one) is the primary male anabolic–androgenic steroid.…”
mentioning
confidence: 99%
“…They were shown to belong to the non-centrosymmetric orthorhombic P2 1 2 1 2 1 , and monoclinic P2 1 space groups. Structural features were described and evaluated in terms of Hirshfeld surfaces, and crystal energies were further compared with the base native form (without ester) and with the acetate ester [ 18 ]. The investigation of crystals in the solid state via computational methods yielded that, in all crystals, the crystal stability and formation of supramolecular self-assemblies are governed by dominant dispersion effects.…”
mentioning
confidence: 99%
See 2 more Smart Citations